Behavioral intention of birdwatchers towards birdwatching activity in Malaysia - Abdul Rahim, Al-Kautsar Hidayanto (2019)
Birdwatching activities can have a positive and negative impact on bird’s wildlife's daily lives. The purpose of this study was to identify the key in encouraging human or birdwatchers towards birdwatching activities in the context of habitat disturbance and threats. The theory used is Theory of Planned Behavior (TPB). This theory is able to provide explanations and reveals the major predictors that influence bird observer in Malaysia towards behavior to birds. Therefore, this study assesses the behavior of birdwatchers towards birdwatching activities. A total of 100 questionnaires have been answered through a Google Form that is distributed to all birdwatching Facebook groups of MNS in Malaysia. The variables from the theory were measured using the 5 -point Likert Scale. Birdwatchers socio-demographics are also identified. Overall, Perceived Behavioral Control (β = 0.598) was the strongest driver of Behavioral Intention (β = 0.202) compared to Subjective Norm and Attitudes (β = 0.023) using the method of path estimation analysis. Birdwatching categories were also significant with behavioral intentions (p-value = 0.01) where p-value is less than 0.05.